As contribuições de Bertha Lutz para o feminismo, a ciência e a sociedade - Santos, Juliana de Oliveira (2024)
This research focuses on the trajectory of scientist and feminist Bertha Lutz and the contributions she made to science, feminism and society. During the research, we noticed that Bertha Lutz had a careful education, planned by her parents, being able to complete her higher studies at the French university Sorbonne. Part of her life Bertha also lived in England and spent some time in the United States, which brought her into contact with the suffragette movement. Understanding that this movement had a lot to offer in the field of female emancipation, Bertha joined it and brought it to Brazil. Here, she was a secretary at the National Museum, having entered through a public examination, something rare for a woman at the time. Together with her father, Adolpho Lutz, Bertha carried out extensive research on anurans and helped her father publish several studies. Thus, by studying a woman who stands out in science, we offer a contribution to the History of Science, regarding the Lutz legacy. This dissertation is divided into two chapters: in the first we tell the story and trajectory of Bertha Lutz to establish herself as a scientist and feminist, in the second we talk about the contribution of her scientific work to the country's scientific communities. The relevance of this work is to show Bertha's trajectory and her insertion in a world considered masculine. The methodology was bibliographic and documentary research using the internet network